The role of confocal laser endomicroscopy in pediatric gastrointestinal diseases: a narrative review - Dalpiaz, Irene; Scarallo, Luca; Andreini, Marco; Renzo, Sara; Russo, Giusy; Ruggiero, Cosimo; Volpe, Danila; Lionetti, Paolo; Oliva, Salvatore (Frontiers in Pediatrics, 2025)
IntroductionConfocal laser endomicroscopy (CLE) is an innovative tool that enables microscopic evaluation of the gastrointestinal mucosa during the digestive endoscopy, providing real-time diagnostic information alongside histopathological findings.MethodsA literature search on CLE in pediatric gastroenterology was performed.ResultsCLE has a broad range of applications, spanning from the upper digestive tract to the lower digestive tract, but its applications in the pediatric setting remains largely unexplored and confined to experimental setting.DiscussionDespite the extensive potential of CLE, its application in pediatric patients has been poorly investigated. This narrative review aims to consolidate the current knowledge on CLE in gastrointestinal diseases and to draw insights from adult studies to promote future research in the pediatric field.